The global impact of the COVID‐19 pandemic on the management and course of chronic urticaria. Issue 3 (29th December 2020) - Kocatürk, Emek; Salman, Andaç; Cherrez‐Ojeda, Ivan; Criado, Paulo Ricardo; Peter, Jonny; Comert‐Ozer, Elif; Abuzakouk, Mohamed; Agondi, Rosana Câmara; Al‐Ahmad, Mona; Altrichter, Sabine; Arnaout, Rand; Arruda, Luisa Karla; et al.
Abstract: Introduction: The COVID‐19 pandemic dramatically disrupts health care around the globe. The impact of the pandemic on chronic urticaria (CU) and its management are largely unknown. Aim: To understand how CU patients are affected by the COVID‐19 pandemic; how specialists alter CU patient management; and the course of CU in patients with COVID‐19. Materials and Methods: Our cross‐sectional, international, questionnaire‐based, multicenter UCARE COVID‐CU study assessed the impact of the pandemic on patient consultations, remote treatment, changes in medications, and clinical consequences. Results: The COVID‐19 pandemic severely impairs CU patient care, with less than 50% of the weekly numbers of patients treated as compared to before the pandemic. Reduced patient referrals and clinic hours were the major reasons. Almost half of responding UCARE physicians were involved in COVID‐19 patient care, which negatively impacted on the care of urticaria patients. The rate of face‐to‐face consultations decreased by 62%, from 90% to less than half, whereas the rate of remote consultations increased by more than 600%, from one in 10 to more than two thirds. Cyclosporine and systemic corticosteroids, but not antihistamines or omalizumab, are used less during the pandemic. CU does not affect the course of COVID‐19, but COVID‐19 results in CU exacerbation in one of three patients, with higher rates in patients with severe COVID‐19. Conclusions: The COVID‐19 pandemic brings major changes and challenges for CU patients and their physicians. The long‐term consequences of these changes, especially the increased use of remote consultations, require careful evaluation. Abstract : The COVID‐19 pandemic severely impairs CU patient care, weekly number of patients decreased by more than 50%, and the rate of face‐to‐face consultations decreased by 62%. CU does not affect the course of COVID‐19 with only 4% of CU patients having a severe course of COVID‐19, but COVID‐19 results in CU exacerbation in one of three patients, with higher rates in patients with severe COVID‐19. Cyclosporine and systemic corticosteroids, but not antihistamines or omalizumab, are used less during the pandemic. Abbreviations: CU, chronic urticarial; COVID‐19, coronavirus disease 2019; UCARE: urticaria centers of reference and excellence.